Aesthetic aspects of adjacent maxillary single-crown implants—influence of zirconia and titanium as implant materials. Issue 11 (November 2020) - Kniha, K.; Bock, A.; Peters, F.; Heitzer, M.; Modabber, A.; Kniha, H.; Hölzle, F.; Möhlhenrich, S.C.
Abstract: The purpose of this retrospective survey was to assess the esthetic aspects of adjacent zirconia and titanium implants in the anterior maxillary area. A total of 40 patients and 109 adjacent implants (17 patients with 47 titanium implants and 23 patients with 62 zirconia implants) was included. The primary aim of this survey was to assess the papillary fill (Jemt score). Additionally, further esthetic aspects were assessed. Papillae were fully present (Jemt score 3) around 39.1% of adjacent zirconia implants and 17.4% of adjacent titanium implants (p < 0.01). The papilla deficit was significantly higher 1.64 mm (SD 1.35) around titanium compared to zirconia implants 0.92 mm (SD 0.94, p < 0.01). The evaluation of the soft tissue recessions revealed no differences between implant materials, whereas titanium implants presented more visible implant shadows (p < 0.01). Zirconia implants had more implants with papillae that filled the entire proximal space compared to titanium implants. Furthermore, titanium implants had a greater frequency of visible implant shadowing than the zirconia implants. Esthetic rules such as the interdental contact area and golden percentage rules did not differ significantly between the titanium and zirconia implants.